Implications of insights from behavioral economics for macroeconomic models - Steinar Holden (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2012)
During the last 20 years, the importance of a number of behavioral features has been widely accepted within economics, and they are now regularly included in standard macro models. Where has this development led us? I argue that the insights from behavioral economics have led to important progress in our understanding of macroeconomic phenomena. One of the most important is the effect of fairness considerations on wages and employment relationships. Another important insight is that most or all individuals are affected by various behavioral features, which should be taken into account in the design of saving plans and pension schemes. A third insight is that plausible macro models provide large scope for the effects of sentiments and psychological factors. Future research should follow different routes, like incorporating behavioral features in standard models, improving estimated empirical models, and learning from case studies and historical episodes.
urn:nbn:de:101:1-201211143689
Keywords: E2; E3; D8; 330; Behavioral macroeconomics